CONTENT AND FORM OF IMPLEMENTATION OF INNOVATIVE PROCESSES IN THE AGRICULTURAL ENTREPRENEURSHIP - Artem Petrov (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the relevance and need for the development of innovative processes in the agricultural business, expanded forms of implementing the example of foreign countries on the need for the development of technology platforms as a communication tool for strengthening the building of the promising commercial technologies, new products, to attract additional resources for innovation activity.